Population Genetic Structure of Three Cichlids in ‎Ilorin, North-Central Nigeria - Iyiola, Oluyinka A; Shaibu, Rahmat D; Oladipo, Segun O; Kareem, Kazeem O; Nneji, Lotanna M; Adeola, Adeniyi C; Anifowoshe, Abass T ‎; Matouke, Moise M (The Iraqi Journal of Veterinary Medicine, 2022)
Cichlids are among the economically important which serve as a source of food for people ‎around the world. A deep understanding of the population structure and genetic diversity of ‎cichlids are vital for initiation of conservation policies and sustainable aquaculture. There is ‎paucity of information on the patterns of genetic variations among and within cichlids in ‎North-central Nigeria. This study, therefore, investigated population genetic structure of ‎Coptodon zillii, Oreochromis niloticus, and Hemichromis fasciatus collected from different ‎freshwater bodies in North-central Nigeria. Genomic DNA was extracted, and five highly ‎polymorphic RAPD primers were used for RAPD-PCR amplification and genotyping of the ‎fish. Genetic polymorphism within and between the three tilapia species were examined. ‎Percentages of polymorphism loci, pairwise population matrix, analysis of molecular variance ‎‎(AMOVA), and genetic distances of cichlid populations were determined using standard ‎methods, and dendrograms were constructed using an un-weighted pair group method of ‎arithmetic mean (UPGMA). Overall, percentages of estimated molecular variance within and ‎among C. zillii, H. fasciatus and O. niloticus populations were 5% and 95%; 4% and 96% and ‎‎13% and 87%, respectively. Our results suggest that the three cichlids have close evolutionary ‎relationship and there were no distinct genetic differences on the basis on sampling locations. ‎C. zillii and H. fasciatus are more genetically closer than O. niloticus. This study concludes that ‎RAPD is useful in studying the population genetic structure of cichlids. This study therefore ‎recommends conservation of genetic pool of cichlid species through proper maintenance and ‎restoration of polluted habitat to guarantee sustainable fishery production. However, markers ‎such as microsatellite DNA can be assayed in further studies for better results‎.